20S-Hydroxyvitamin D3, a Secosteroid Produced in Humans, Is Anti-Inflammatory and Inhibits Murine Autoimmune Arthritis - Postlethwaite, Arnold E.; Tuckey, Robert C.; Kim, Tae-Kang; Li, Wei; Bhattacharya, Syamal K.; Myers, Linda K.; Brand, David D.; Slominski, Andrzej T. (Frontiers in Immunology, 2021)
The ability to use large doses of vitamin D3 (D3) to chronically treat autoimmune diseases such as rheumatoid arthritis (RA) is prohibitive due to its calcemic effect which can damage vital organs. Cytochrome P450scc (CYP11A1) is able to convert D3 into the noncalcemic analog 20S-hydroxyvitamin D3 [20S(OH)D3]. We demonstrate that 20S(OH)D3 markedly suppresses clinical signs of arthritis and joint damage in a mouse model of RA. Furthermore, 20S(OH)D3 reduced lymphocyte subsets, cytokines, and anti-type II collagen antibodies implicated in this model. These results provide a basis for further consideration of 20S(OH)D3 as a potential treatment for RA and other autoimmune disorders.